An insight of fiber role in allergy - Endah Citraresmi (Indonesian Nutrition Association, 2022)
Dietary fiber is a complex dietary component, including carbohydrate polymers and oligomers, that resists digestion in the small bowel and enters the large bowel intact and fermented by the bacteria.